IL-15–PI3K–AKT–mTOR: A Critical Pathway in the Life Journey of Natural Killer Cells - Ali, Alaa Kassim; Nandagopal, Neethi; Lee, Seung-Hwan (Frontiers in Immunology, 2015)
Among numerous cytokines modulating Natural Killer (NK) cell function, Interleukin 15 (IL-15) exerts a broad range of effect from development and homeostasis, to activation of mature NK cells during infection. Its significance is further highlighted by clinical trials in which IL-15 is being used to boost the proliferation and anti-tumor response of NK cells. Among the signal transduction pathways triggered by the engagement of IL-15 receptor with its ligand, the PI3K-AKT-mTOR pathway seems to be critical for the IL-15 mediated activation of NK cells, therefore being responsible for efficient anti-viral and anti-tumor responses. This review provides an overview of the role of IL-15 at multiple stages of NK cell life journey. Understanding the pathway by which IL-15 conveys critical signals for the generation of NK cells with efficient effector functions, in combination with established protocols for NK cell expansion ex vivo, will undoubtedly open new avenues for therapeutic applications for immunomodulation against infections and cancers.